2020
DOI: 10.1002/pon.5399
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel telemedicine‐based intervention to manage body image disturbance in head and neck cancer survivors

Abstract: Objectives: The study aimed to evaluate the feasibility, acceptability, and preliminary clinical impact of BRIGHT (Building a Renewed ImaGe after Head & neck cancer Treatment), a novel telemedicine-based cognitive-behavioral intervention to manage body image disturbance (BID) in head and neck cancer (HNC) survivors. Methods: Head and neck cancer survivors with BID were enrolled into a single-arm pilot trial. Participants completed study measures at baseline, 1-and 3-months post-BRIGHT to assess its acceptabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(65 citation statements)
references
References 31 publications
1
64
0
Order By: Relevance
“…Stigma is generally likely for people with altered appearance regardless of gender [45]; however, it is possibly harder for men to disguise an altered appearance as they tend not to use makeup, scarves or other accessories which could hide the area. Being able to camouflage visible altered appearance has been found to lower distress for female survivors of HNC [46], however, Graboyes et al point to the inability of cosmetic interventions to effectively address complex psychosocial aspects of body image disturbance [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stigma is generally likely for people with altered appearance regardless of gender [45]; however, it is possibly harder for men to disguise an altered appearance as they tend not to use makeup, scarves or other accessories which could hide the area. Being able to camouflage visible altered appearance has been found to lower distress for female survivors of HNC [46], however, Graboyes et al point to the inability of cosmetic interventions to effectively address complex psychosocial aspects of body image disturbance [7].…”
Section: Discussionmentioning
confidence: 99%
“…Research on survivors of HNC has shown that altered appearance is a source of psychological distress [1,5]. Changes in appearance and function can be the result of surgery [6] and chemo-radiotherapy [7]. Surgical treatment to the face and neck has been found to create negative changes in autoperceived body image in 1/3 of survivors with head and neck cancer (n = 36) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey data were qualitatively and statistically interpreted to describe the impact of COVID- 19 AK, HI). The status of the survey responder was defined as a patient undergoing active treatment, a caregiver of a patient speaking on behalf of the patient, or a patient in the survivorship period (\2, 2-5, or .5 years from the end of treatment).…”
Section: Data Reporting and Statistical Analysismentioning
confidence: 99%
“…The social distancing restrictions of COVID-19 and the impact on health care, including delays in treatment and cancelations of routine clinic visits, may also affect patients with HNC and have long-lasting consequences on psychosocial and physical health. [5][6][7][8] Yet, these precautionary measures may be especially prudent to follow as providers may be more at risk for infection and patients may be more at risk of severe sequelae from COVID- 19.…”
mentioning
confidence: 99%